Evaluating customers’ acceptance on electronic payment system in Algeria - Alaeddine, Ziouache (2020)
The enormous increase in demand for online payment in Algeria among the bank's customers had subsequently increased the concern among the customers of the banks and the Algerian government about the importance of the significant variables that affect the customers intention to utilize the online payment. This concern, have led to do this study in order to focus on identifying the most crucial factor that effectively influences the Algerian banks customers in using the digital payment more compared to the conventional tools, to gain advantages like saving efforts and time also money. Because of this, the purpose of this paper is to determine the most crucial factors that have significant relationship with the online payment intention among the banks customers in Algeria by using the technology acceptance model (TAM) in the proposed model. There were five independent variables that have been investigated in this study including trust towards online payment, security, ease of use, lack of awareness, and IT infrastructure. A total of 250 questionnaires were distributed among the Algerian banks customers by using clustered sampling, to perform the statistical analysis for data analysis and findings. The results indicated the trust towards online payment has a significant effect on digital payment intention among the Algerian banks customers. However, security, ease of use, lack of awareness, IT infrastructure showed insignificant influence towards the e-payment intention. Among all predictors, trust towards electronic payment has the most strong influence on the digital payment intention among the Algerian banks customers.